Enhanced supercapacitive performance of reduced graphene oxide by incorporating NiCo2O4 quantum dots using aqueous electrolyte. (10th June 2021) - Siwatch, Poonam; Sharma, Kriti; Singh, Navjot; Manyani, Nirmal; Tripathi, S.K.
Abstract: We have prepared nanocomposite films of reduced graphene oxide (rGO) and nickel cobalt oxide quantum dots (NCO-QDs) by chemical method, and these are represented by NCO-rGO. Different nanocomposite films have been formed by varying the ratio of NCO-QDs and rGO. The obtained value of the specific capacitance of the nanocomposite (NCO5 -rGO1.5 ) is 265 F g − 1 (260 C g − 1 ) at 0.73 A g − 1 which is much higher than rGO alone (96 F g − 1 at 0.33 A g − 1 ). As the asymmetric/hybrid configuration also enhances the potential window, so in this work, we have fabricated an asymmetric supercapacitor with NCO5 -rGO1.5 as the positive electrode and rGO as a negative electrode using 1 M Na2 SO4, neutral aqueous solution, as the electrolyte. The assembled supercapacitor delivered the specific capacitance value of 131 F g − 1 (197 C g − 1 ) at an energy density of 47 W h kg −1 and a power density of 631 W kg −1 within a wide potential window of 1.6 V. The potential window of the device can be extended up to 2.4 V, but in that case, its coulombic efficiency decreases. The device retains a specific capacitance of 69% after 1000 cycles of charge-discharge. Also, a solid-state device has been fabricated, which displays a potential of 3.4 V after charging 20 s. All these results may prove fruitful for the design of high energy density supercapacitors in the future. Graphical abstract: Image, graphical abstract